Health Systems Capacity for Couple Focused Approach to Family Planning in the New Juabeng Municipality - Owusu, S. K. (University of Ghana, 2010)
Introduction: The concept of health systems deals with the issues of governance, information, medicines and technologies, financing, human resource and service delivery. However this study focuses only on the human resource and the service delivery aspects of the health systems. Studies have made it clear that counseling couples together about family planning influences correct use of methods, and their continuation, bringing about high success rates and satisfaction in family planning. In Ghana although the total fertility rate for women 15-49 is 4.0 births per woman, the contraceptive prevalent rate is only 24% and the level of couple involvement in family planning is low in Ghana (GDHS, 2008). Having low contraceptive prevalence rate may imply that there are still high unmet needs and more women are resorting to abortions to control their fertility. (Almualm, 2007). Aim: The study set out to explore the Health Systems‘ capacity in the New Juabeng Municipality towards implementing Couple Focused Approach to Family Planning. Methods: It was a cross-sectional, descriptive, qualitative and quantitative research. Purposive and convenience sampling was used in selecting the study group because it was realized that although there were quite a number of clients who practice family planning, many of the women were doing so secretly. A total of 148 clients (135 female and 11 males) who had visited the clinic for at least 2 times and had both couple in agreement were interviewed using both open and closed ended questionnaires but 2 of the responses were rejected and 146 were used for the analysis. There were 6 key informants who were also interviewed on the subject. The responses were coded and analysed using Epi Info software version 3.4.1 and Microsoft Office Excel 2007. Descriptive statistics using charts, graphs and frequency tables were employed to present the results. Results: The result of the study has shown that the Municipality is doing quite well in family planning in general. However, the concept of Couple Focused Approach seems to be a new concept that most of the providers are not familiar with let alone knowing what it entails. The providers need additional training to be able to deliver the couple focused approach to family planning. The responses from both the providers and the clients during the interviews suggest that adequate counseling should be given to the clients to enhance couple focused approach to family planning. Conclusion: In the era where Ghana is advocating for repositioning of family planning it is important to consider adopting the Couple Focused Approach to Family Planning in the Municipality to enhance the uptake of family planning
Thesis (MPH) - University of Ghana, 2010.
Keywords: Health Systems; Family Planning; New Juabeng; Couple Focused